Strengthening the United States' Database Protection Laws: Balancing Public Access and Private Control. - Resnik, David B. (Science & Engineering Ethics, 2003)
This paper develops three arguments for increasing the strength of database protection under U.S. law. First, stronger protections would encourage private investment in database development, and private databases have many potential benefits for science and industry. Second, stronger protections would discourage extensive use of private licenses to protect databases and would allow for greater public control over database laws and policies. Third, stronger database protections in the U.S. would harmonize U.S. and E.U. laws and would thus enhance international trade, commerce, and research. The U.S. should therefore follow the European example and develop two tiers of protection for databases: 1) protection for creative databases under copyright law; 2) protection for non-creative databases through a special type of sui generis protection. In order to balance private control of data and public access to data, sui generis protections should define a "fair use" exemption that permits some unauthorized extraction of data for private, educational, and research purposes, provided that such extraction does not adversely impact the economic value of the database.